PENGARUH KEBIJAKAN DIVIDEN, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Iswara, Ulfah Setia; Setyabudi, Teguh Gunawan; Palupi, Dian (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
This study aims to test and prove empirically the effect of dividend policy, profitability and leverage on firm value. Quantitative research uses secondary data in the form of financial statement data and annual reports of companies belonging to the manufacturing industry sector listed on the Indonesia Stock Exchange. The research was conducted in the period 2019 to 2021 with a total of 138 companies. Data analysis using multiple regression analysis. The results showed that dividend policy has a significant positive effect on firm value. There is a significant positive effect of profitability on the value of the company. Leverage is also proven to have a significant effect on firm value.